Contrasting effects of maize litter and litter-derived biochar on the temperature sensitivity of paddy soil organic matter decomposition - Cui, Jun; Ge, Tida; Nie, Ming; Kuzyakov, Yakov; Alharbi, Sulaiman; Fang, Changming; Deng, Zifa (Frontiers in Microbiology, 2022)
Organic matter input regulates the rate and temperature sensitivity (expressed as Q10) of soil organic matter (SOM) decomposition by changing microbial composition and activities. It remains unclear how the incorporation of litter-made biochar instead of litter affects the Q10 of SOM decomposition. Using a unique combination of two- and three-source partitioning methods (isotopic discrimination between C3/C4 pathways and 14C labeling), we investigated: (1) how maize litter versus litter-made biochar (of C4 origin) addition influenced the Q10 of SOM (C3 origin) under 10 °C warming, and (2) how the litter or biochar amendments affected the Q10 of 14C-labeled fresh organic matter (FOM) after long-term incubation. Compared with biochar addition, litter increased the rates and Q10 of mass-specific respiration, SOM and FOM decomposition, as well as the contents of SOM-derived dissolved organic C (DOC) and total phospholipid fatty acids (PLFA). Litter-amended soils have much higher activities (Vmax) of β-glucosidase, N-acetyl-β-glucosaminidase, and leucine aminopeptidase, suggesting larger enzyme pools than in soils with biochar. The Q10 of enzyme Vmax (1.6–2.0) and Km (1.2–1.4) were similar between litter- and biochar-amended soils, and remained stable with warming. However, warming reduced microbial biomass (PLFA) and enzyme activity (Vmax), suggesting decreased enzyme production associated with smaller microbial biomass or faster enzyme turnover at higher temperatures. Reductions in PLFA content and enzyme Vmax due to warming were larger in litter-amended soils (by 31%) than in the control and biochar-amended soils (by 4–11%), implying the active litter-feeding microorganisms have a smaller degree of heat tolerance than the inactive microorganisms under biochar amendments. The reduction in enzyme activity (Vmax) by warming was lower in soils with biochar than in the control soil. Our modeling suggested that the higher Q10 in litter-amended soils was mainly caused by faster C loss under warming, linked to reductions in microbial biomass and growth efficiency, rather than the slightly increased SOM-originated substrate availability (DOC). Overall, using straw-made biochar instead of straw per se as a soil amendment lowers the Q10 of SOM and FOM by making microbial communities and enzyme pools more temperature-tolerant, and consequently reduces SOM losses under warming.